My friend May - Flett, Julie (Greystone Kids/Greystone Books, 2025)
A little girl named Margaux has a big black cat named May. One day, May doesn't come home for dinner and, although the family looks and looks, they can't find her. Margaux's auntie helps in the search, but she can't stay long because she is packing to move to the city. Margaux will miss her auntie. She also misses May. Will May ever come home?